2014
DOI: 10.4041/kjod.2014.44.5.246
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced compatibility and initial stability of Ti6Al4V alloy orthodontic miniscrews subjected to anodization, cyclic precalcification, and heat treatment

Abstract: ObjectiveTo evaluate the bioactivity, and the biomechanical and bone-regenerative properties of Ti6Al4V miniscrews subjected to anodization, cyclic precalcification, and heat treatment (APH treatment) and their potential clinical use.MethodsThe surfaces of Ti6Al4V alloys were modified by APH treatment. Bioactivity was assessed after immersion in simulated body fluid for 3 days. The hydrophilicity and the roughness of APH-treated surfaces were compared with those of untreated (UT) and anodized and heat-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
2
28
0
3
Order By: Relevance
“…Many methods including surface treatments such as polishing and modification of surface free energy10111213 have been employed to reduce or nullify the bacterial aggregation around titanium-based prosthesis. Elemental silver has been specifically known for its array of antimicrobial properties for many years 14.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods including surface treatments such as polishing and modification of surface free energy10111213 have been employed to reduce or nullify the bacterial aggregation around titanium-based prosthesis. Elemental silver has been specifically known for its array of antimicrobial properties for many years 14.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed to modify the surface characteristics of titanium implants for improving the osseointegration. One of surface modifications is an anodic oxidation that is a well-established surface modification technique for value metals [8][9][10]13]. Anodized TiO 2 films may have different mechanical and chemical characteristics by different treatment conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon also occurs on the surfaces of bioactive glass and glass ceramics [7,8]. Research showed that high degree of bone contact and bone formation was achieved with anodized titanium surface [9][10][11]. Saldana et al reported that the ability of human osteoblasts to differentiate when cultured on thermally oxidized titanium alloy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al29 reported that the Ca/P ratio was above 1.5 in the early stage of placement of implant, because of the presence of newly formed bone. The difference probably arises from the fact that transmission electron microscopy was used, which is able to detect newly formed bone, unlike the SEM33 that we used in this study. This could be considered a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%